Habitat fragmentation has some impacts on aspects of ecosystem functioning in a sub-tropical seagrass bed. (May 2017) - Sweatman, Jennifer L.; Layman, Craig A.; Fourqurean, James W.
Abstract: Habitat fragmentation impacts ecosystem functioning in many ways, including reducing the availability of suitable habitat for animals and altering resource dynamics. Fragmentation in seagrass ecosystems caused by propeller scarring is a major source of habitat loss, but little is known about how scars impact ecosystem functioning. Propeller scars were simulated in seagrass beds of Abaco, Bahamas, to explore potential impacts. To determine if plant-herbivore interactions were altered by fragmentation, amphipod grazers were excluded from half the experimental plots, and epiphyte biomass and community composition were compared between grazer control and exclusion plots. We found a shift from light limitation to phosphorus limitation at seagrass patch edges. Fragmentation did not impact top-down control on epiphyte biomass or community composition, despite reduced amphipod density in fragmented habitats. Seagrass and amphipod responses to propeller scarring suggest that severely scarred seagrass beds could be subject to changes in internal nutrient stores and amphipod distribution. Highlights: Propeller scars were simulated in continuous seagrass beds. Seagrasses at fragment interiors show signs of light-limitation. Amphipod density was reduced in seagrass fragments. Amphipod community structure was not affected by fragmentation. Top-down control by amphipods on epiphytes was not affected by fragmentation.